2008
DOI: 10.1073/pnas.0804507105
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of a myelodysplastic syndrome by a long-term repopulating hematopoietic cell

Abstract: The myelodysplastic syndromes (MDS) comprise a group of premalignant hematologic disorders characterized by ineffective hematopoiesis, dysplasia, and transformation to acute myeloid leukemia (AML). Although it is well established that many malignancies can be transplanted, there is little evidence to demonstrate that a premalignant disease entity, such as MDS or colonic polyps, can be transplanted and subsequently undergo malignant transformation in vivo. Using mice that express a NUP98-HOXD13 (NHD13) transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…17 To define the hematopoietic subsets affected by apoptosis in NHD13 mice, we measured the numbers and percentages of cells undergoing apoptosis among defined hematopoietic stem and progenitor cells by flow cytometry. As previously reported, 18,19 the proportions of Lineage neg Sca-1 + c-Kit + (LSK) stem/multi-potent progenitor cells and Lineage neg Sca-1 − c-Kit + (LK) progenitor cells were reduced approximately three-fold and two-fold, respectively (Figure 1a). Using the Signaling Lymphocyte Activation Molecules (SLAM) CD48 and CD150, we found that longterm (LT)-HSCs (LSK,CD150 + CD48 − ) and short-term (ST)-HSCs (LSK, CD150 − CD48 − ) were more markedly reduced (410-fold) in proportion and absolute numbers than multipotent progenitors, MPP (LSKCD150 − CD48 + ) (Figures 1a and b).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…17 To define the hematopoietic subsets affected by apoptosis in NHD13 mice, we measured the numbers and percentages of cells undergoing apoptosis among defined hematopoietic stem and progenitor cells by flow cytometry. As previously reported, 18,19 the proportions of Lineage neg Sca-1 + c-Kit + (LSK) stem/multi-potent progenitor cells and Lineage neg Sca-1 − c-Kit + (LK) progenitor cells were reduced approximately three-fold and two-fold, respectively (Figure 1a). Using the Signaling Lymphocyte Activation Molecules (SLAM) CD48 and CD150, we found that longterm (LT)-HSCs (LSK,CD150 + CD48 − ) and short-term (ST)-HSCs (LSK, CD150 − CD48 − ) were more markedly reduced (410-fold) in proportion and absolute numbers than multipotent progenitors, MPP (LSKCD150 − CD48 + ) (Figures 1a and b).…”
Section: Resultssupporting
confidence: 84%
“…16 The presence of self-renewing cells capable of generating MDS was demonstrated by transplantation of NHD13 bone marrow cells. 19 However, the phenotype of these cells was not defined beyond the absence of lineage markers; a population that includes both HSCs and committed progenitors. Therefore, we transplanted into lethally irradiated recipients, immature HSC subsets including LT-HSCs or MPPs and more terminally differentiated and mature LK cells to define which cell is most relevant for our studies on the role of apoptosis in leukemic transformation (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…by guest www.bloodjournal.org From transgenic mice, both models of progenitor-derived malignancies. 29,34 In contrast, the NHD13 acute myeloid leukemias are probably derived from HSCs, 35 which respond differently to DNA damage. 36 Recently, we have shown that blocking apoptosis by BCL2 (or absence of Puma) prevents the development of ␥-radiationinduced thymic lymphoma.…”
Section: Bcl2 Prevents Transformation Of Mds 2481mentioning
confidence: 99%
“…The genetic manipulations used to generate these models include gene deletion (Asxl1, CD74-Nid67, Bap1, Dicer, Dnmt3a, Map3k7/Tak, miR145/146a, and Npm1), 50-58 overexpression (mutated Asxl1, Evi1, Nup98-Hox13D, mutated Runx1, human [h]SALL4b, hS100A9, Bcl2 1 mutated NRAS and Traf6), 1,56,[59][60][61][62][63][64][65] and mutation (CyclinE and Polg). 66,67 All but 4 of these genes have corresponding alterations in human MDS (or MDS/MPN) patients (Table 3).…”
Section: Mouse Models With Dysplasia In One or More Hematopoietic Linmentioning
confidence: 99%
“…Myelodysplastic syndrome (MDS) represents a heterogeneous group of hematopoietic stem cell (HSC)-based disorders, [1][2][3] characterized by peripheral blood (PB) cytopenias of $1 lineage, bone marrow (BM) hypercellularity, and cytologic dysplasia. 4 The term myelodysplasia encompasses all morphologic abnormalities in the affected myeloid lineage(s); its presence is a key distinguishing feature for the diagnosis of MDS.…”
Section: Introductionmentioning
confidence: 99%